‘I am a father but not pregnant’: a qualitative analysis of the perspectives of pregnant couples on male partner role during pregnancy care in Bamenda, Cameroon - Lily Haritu Foglabenchi; Heidi Stöckl; Tanya Marchant (Reproductive Health)
Abstract Background The reduction of maternal mortality has stagnated globally. Estimates project a rise to 140.9 deaths per 100,000 live births by 2030, which is double the Sustainable Development Goal target. Male involvement in pregnancy care has been proposed as an intervention to improve maternal and child health outcomes. However, there is limited understanding of how communities view the role of men beyond the instrumentalist approach that only targets men as accompanying partners without altering the underlying gender and socio-cultural determinants that shape their involvement in pregnancy care. This study broadens existing research by exploring and and contextualising the role of male partners during pregnancy in Bamenda, Cameroon. Methods This study employed a qualitative design underpinned by symbolic interactionism. We conducted 68 semi-structured interviews (SSIs) and three focus group discussions (FGDs) with purposively selected pregnant women (n = 38 SSIs; n = 2, FGD) and male partners (n = 30 SSIs; n = 1, FGD) in an urban hospital in the North West Regional capital—Bamenda. Nvivo was used for data management and subsequently, we performed thematic analysis using a critical discourse lens to generate manifest and latent interpretations of study findings. Results The role of male partners reflected hegemonic masculinity and was broadly conceptualised in three categories: breadwinner, protector/comforter, and ‘sender’ for antenatal care. Perceptions of men’s role differed between male and female participants. While women sought male involvement for pragmatic reasons like joint attendance of antenatal care, psychosocial support (affirmation) and assistance with domestic chores, men limited their involvement to roles that matched gendered preconceptions of masculinity like financial support for antenatal fees, maternal nutrition and birth supplies. Nonetheless, the perceived benefits for antenatal attendance was expressed by some men in terms of the direct access it gives them to pregnancy-related education from experts, paternal bonding and the appeal of fast-track services for couples. Conclusion Male involvement in maternal and child health in Bamenda Health District is an extension and reflection of how patriarchal norms on masculinity are constructed and adapted in this setting. To address gaps in male involvement, intervention designers and implementers will need to take into account prevailing culture-specific norms while deconstructing and leveraging masculine ideals to situate male involvement in the prenatal context.